Taking a stand against agism: Appeal to the policymakers - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Annals of Medical Science and Research)
Globally, people are living longer with the speed of aging is quite quicker than what was observed in earlier decades. The findings of a recently released report suggest that negative attitudes toward older people are widely prevalent and even have been associated with hazardous impacts on their physical and mental health. The need of the hour is to stop labeling people as elderly and discriminating them or associating some things just due to their age factor. At the same time, there is a great need to address the prevailing negative attitude of health-care professionals toward the elderly. In fact, a global strategy has been formulated and adopted by the member states of the World Health Organization to combat aging successfully by 2030. To conclude, to have more prosperous, equitable, and healthier societies in the future, it is high time to stop categorizing people based on their age and this can happen only when ageist prejudices are eliminated forever.